Photocrosslinking of human telomeric G-quadruplex loops by anti cyclobutane thymine dimer formation - Su, Dian G. T. (National Academy of Sciences, 2009)
The unusual structural forms of telomere DNA, which protect the ends of chromosomes during replication, may render it vulnerable to unprecedented photodamage, possibly involving nonadjacent bases that are made proximate by folding. The G-quadruplex for the human telomere sequence consisting of a repeating d(TTAGGG) is one unusual form. Tel22, d[AGGG(TTAGGG)(3)], forms a basket structure in the presence of Na(+) and may form multiple equilibrating structures in the presence of K(+) with hybrid-type structures predominating. UVB irradiation of d[AGGG(TTAGGG)(3)] in the presence of Na(+) results in a cis,syn thymine dimer between two adjacent Ts in a TTA loop and a mixture of nonadjacent anti thymine dimers between various loops. Irradiation in the presence of K(+), however, produces, in addition to these same products, a large amount of specific anti thymine dimers formed between either T in loop 1 and the central T in loop 3. These latter species were not observed in the presence of Na(+). Interloop-specific anti thymine dimers are incompatible with hybrid-type structures, but could arise from a chair or basket-type structure or from triplex intermediates involved in interconverting these structures. If these unique nonadjacent anti thymine dimer photoproducts also form in vivo, they would constitute a previously unrecognized type of DNA photodamage that may interfere with telomere replication and present a unique challenge to DNA repair. Furthermore, these unusual anti photoproducts may be used to establish the presence of G-quadruplex or quadruplex-like structures in vivo.